Exergy analysis of reverse electrodialysis. (15th May 2018) - Giacalone, F.; Catrini, P.; Tamburini, A.; Cipollina, A.; Piacentino, A.; Micale, G.
Graphical abstract: Highlights: An original Exergy analysis of Reverse electrodialysis unit is reported. All irreversible phenomena within the unit are described using a 1-D model. The effect of each irreversibility source on exergy performance is analysed. The effect of operating conditions on exergetic performance is evaluated. Abstract: Reverse electrodialysis in closed loop configurations is a promising membrane technology in the energy conversion and storage fields. One of the main advantages of closed-loop reverse electrodialysis is the possibility of using a wide range of operating concentrations, flow rates and different salts for generating the salinity gradient. In this work, an original exergy analysis of the reverse electrodialysis process was carried out in order to investigate reverse electrodialysis performance in terms of energetic and exergetic efficiency parameters in a wide range of operating conditions. A mono-dimensional model of the reverse electrodialysis process was developed, in which all sources of irreversibility are considered, such as non-ideal membranes permselectivity, ohmic losses and uncontrolled mixing phenomena (salt and water diffusive flux across membranes). For each of them, the influence on the exergy efficiency is quantified and compared. Results also indicate how exergetic and energetic performance are largely dependent on solutions concentration: when high salinity gradient differences are used within the unit, membrane water permeability heavily affects process performance, thus reducing exergy efficiency, though a larger power output can be normally achieved. The more performing flow arrangement for the stack has been found to be the counter-current, though significant differences are observed only for long channels. Finally, performance is improved when short residence time within the stack is attained for the low-concentration solution.